Keeping Passion Alive While Updating Journalism Skills. (March 2020) - Clark, Chandra; Plakhina, Elena; Rosales, Rey
Educators face a major challenge protecting and nurturing students' passion for journalism while scrambling to help them keep up with a work environment in constant flux. They cannot afford to sidetrack this passion while teaching new software, evolving technology, and marketplace needs. If universities want to produce the best and brightest future journalists, they need to teach the above while nurturing student excitement for the field. This syndicate offers three recommendations to reach this goal: reconsider the traditional learning "box" used for student curricula, evaluate experimentation and its value for the learning process, and engage students in passion projects that prompt critical thinking and problem-solving skills.